Time-varying serum uric acid predicts new-onset atrial fibrillation in treated hypertensive patients. The LIFE Study - Eran S. Zacks; Ildri M. Stokke; Kristian Wachtell; Darcy A. Hille; Aud Høieggen; Sverre E. Kjeldsen; Stevo Julius; Eva Gerdts; Peter M. Okin; Richard B. Devereux (Open Exploration Publishing Inc., 2022)
Aim: The Losartan Intervention For Endpoint reduction in hypertension (LIFE) study showed less new-onset atrial fibrillation (AF) in hypertensive patients receiving losartan- vs. atenolol-based treatment. Because losartan reduces serum uric acid (SUA) levels, the aim of the present study was to investigate relations of SUA with new-onset AF in the study. Methods: Hypertensive patients with electrocardiographic (ECG) left ventricular hypertrophy (LVH) and no prior AF (n = 8,243) were treated for 5.0 ± 0.4 years with losartan- or atenolol-based therapy. Associations of SUA with new-onset AF documented by Minnesota coding were assessed by Cox models using SUA and systolic blood pressure as time-varying covariates to take into account changes of SUA related to losartan or diuretic treatment, changes in renal function, and aging. Results: Time-varying SUA was associated with new AF defined by Minnesota code [hazard ratio (HR) = 1.19 per 16.8 μmol/L (1 mg/dL), (95% confidence intervals (CIs), 1.12-1.26), P < 0.0001], independent of losartan treatment [HR = 0.75 (95% CIs, 0.61-0.93), P = 0.007], older age [HR = 1.95 per 7.0 years (95% CIs, 1.73-2.20), P < 0.0001], male sex [HR = 1.46 (95% CIs, 1.09-1.94), P = 0.010] and higher Cornell voltage-duration product [HR = 1.10 per 1,023 ms·mm (95% CIs, 1.01-1.21), P = 0.034]. Similar results were obtained in Cox models with SUA levels partitioned according to baseline quartiles and in which AF was defined by physician reports or by both Minnesota coding and physician reports. Conclusions: In-treatment SUA is a strong predictor for new-onset AF in hypertensive patients, independent of effects of antihypertensive treatment, age, sex, and ECG-LVH. Further research is needed to clarify how uric acid may provoke AF (ClinicalTrials.gov identifier: NCT00338260).